2016
DOI: 10.1515/bimo-2016-0004
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Genotoxic Effects of Asbestos on Occupationally Exposed Workers in Brazil

Abstract: group and individuals without asbestosis, respectively. Linear regression analysis showed that 28,4% and 50,5% of comet assay results were increased by exposure to asbestos and developed asbestosis. The results of CAT and GST were not difference between the groups. These results supports the association of genotoxic damage and the onset of asbestosis by chrysotile asbestos exposure in workers of this study.Keywords: asbestos, occupational exposure, genotoxicity. IntroductionAsbestosis is a form of pneumoconios… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Data in the literature on oxidative stress enzymes have produced controversial results and reported both increases and decreases of activity under different types of exposure, which calls for further research in this area [34,46,72]. Some studies have also revealed that GST activity may be lower at the beginning of exposure and/or during the development of a given disease, but may subsequently return to normal [80,81].…”
Section: Discussionmentioning
confidence: 99%
“…Data in the literature on oxidative stress enzymes have produced controversial results and reported both increases and decreases of activity under different types of exposure, which calls for further research in this area [34,46,72]. Some studies have also revealed that GST activity may be lower at the beginning of exposure and/or during the development of a given disease, but may subsequently return to normal [80,81].…”
Section: Discussionmentioning
confidence: 99%